The feminism and visual culture reader - Jones, Amelia (Routledge, 2010)
Feminism is one of the most important perspectives from which visual culture has been theorized and historicized over the past forty years. Challenging the notion of feminism as a unified discourse, this second edition of The Feminism and Visual Culture Reader assembles a wide array of writings that address art, film, architecture, popular culture, new media and other visual fields from a feminist perspective. The essays, 40% of which are new to the second edition, are informed by the authors’ deep attention to historical, geographical, and disciplinary contexts as well as by cutting edge concerns such as globalization, diasporic cultural shifts, developments in new media technologies, and intersectional identity politics. The Feminism and Visual Culture Reader combines classic texts with six specially commissioned pieces, all by leading feminist critics, historians, theorists, artists, and activists. Articles are grouped into thematic sections, each of which is introduced by the editor. Providing a framework within which to understand the shifts in feminist thinking in visual studies, as well as an overview of major feminist theories of the visual, this reader also explores how issues of race, class, nationality, and sexuality enter into debates about feminism in the field of the visual
Première publication: 2003
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; arts visuels et médiatiques; cours; discipline; discours dominant; fem1000; genre; har4600; identités LGBTQIA2+; interdisciplinarité; intersectionnalité; premier cycle; périodes historiques; racialisation; sexualité; systèmes d'oppressions; thématiques; théories féministes; études culturelles

La présence lesbienne dans le théâtre féministe québécois des années 1975-1985 chez Marie-Claire Blais, Pol Pelletier et Jovette Marchessault - Laillou Savona, Jeannelle (Voix et Images, 2010)
Le présent article porte sur les personnages lesbiens de quatre « morceaux choisis » du théâtre de la grande période féministe québécoise (1976-1985) : les deux « Marcelle » dans La nef des sorcières, « Les vaches de nuit » dans Triptyque lesbien et La lumière blanche. L’influence de ces personnages est analysée à la lumière de deux idéologies lesbiennes distinctes, toutes deux tributaires des écrits féministes de l’époque et centrées sur les problèmes de la maternité et du genre sexuel. Après une présentation de ces deux courants théoriques, cette étude des personnages souligne aussi les innovations théâtrales qu’ils incarnent en distinguant deux courants esthétiques majeurs : « l’esthétique du combat » (Pelletier) et celle de l’intimité féminine (Marchessault), qui, malgré leur dissemblance, fusionnent souvent de façon originale en enrichissant ainsi le théâtre au féminin de cette période.
Keywords: amériques; arts; discipline; maternité; personnes lesbiennes; québec; ressource en ligne; régions géographiques; sexualité; thématiques; théâtre

An Interview with Dorothy Allison - Lemahieu, Michael (CONTEMPORARY LITERATURE, 2010)
Keywords: arts; discipline; genre; histoire et politique; littérature; mémoire collective; ressource en ligne; sexualité; thématiques; études littéraires